Micro-learning-Based English Learning Videos for Vocational High School Students: Needs Analysis - Lubis, Sofia Idawati; Harahap, Yunita Mutiara; Rahmawati, Wiki Tedi (EXCELLENCE: Journal of English and English Education, 2025)
This study aims to identify the needs of vocational high school students in learning English grammar, particularly focusing on tenses, to support the development of microlearning-based instructional videos. Using Hutchinson and Waters’ (1987) needs analysis theory, the research involved 30 eleventh-grade Accounting students from a vocational high school in Medan. Data were collected through semi-structured interviews and analyzed thematically. The findings show that students perceive English tenses; Simple Present, Simple Past, and Present Perfect as essential for academic tasks and workplace communication. However, they experience significant difficulties in understanding these grammar rules due to the lack of engaging, contextual, and accessible learning media. Students expressed a strong preference for short, visually-rich videos with relatable examples that they can access independently. These results suggest that instructional materials should integrate microlearning principles to address students’ necessities, lacks, wants, and learning preferences. The study recommends the design of microlearning videos embedded with project-based and problem-based learning models to support 21st-century skills.